Spectroscopic ellipsometry of SU‐8 photoresist from 190 to 1680 nm (0.740–6.50 eV). (14th October 2020) - Major, George H.; Chapman, Sean C.; Chapman, Jeffrey T.; Wheeler, Joshua I.; Chatterjee, Shiladitya; Cushman, Cody V.; Ess, Daniel H.; Linford, Matthew R.
Abstract : SU‐8 is an important, epoxy‐based, negative photoresist that can create high aspect ratio features. Spectroscopic ellipsometry (SE) is a nondestructive analytical technique that can be performed in the open air. In this study, reflection and transmission SE measurement data were combined to model the optical function of SU‐8 photoresist. The data were fit using three different models: (i) a B‐spline model, (ii) a four‐Gaussian oscillator model with an ultraviolet (UV) and an infrared (IR) pole, and (iii) a Cody–Lorentz model with three additional Gaussian oscillators. All three models successfully fit the data, where the B‐spline model showed the lowest mean squared error. In situ SE data were also collected and fitted to follow possible changes in the optical properties of the SU‐8 during its development. Time‐dependent density functional theory (TD‐DFT) modeling of a complete SU‐8 monomer is qualitatively and quantitatively consistent with the measured optical function.